Pengembangan Instrumen Penilaian Untuk Pembelajaran Matematika Berbasis Pjbl Pada Sekolah Penggerak Di Kabupaten Manokwari - Irfan Irnandi; Nahrun Najib Siregar; Andi Fajeriani Wyrasti (Jurnal THEOREMS (The Original Research of Mathematics), 2023)
One of the important components in educational evaluation is assessment. This study aims to develop an assessment instrument for PjBL-based learning in mathematics at a driving school in Manokwari district. The research method used by the researcher is research and development with a 4D development model (Define, Design, Develop, and Disseminate). This research procedure consists of this includes 4 stages, namely the stage of defining (define), design (design), development (develop) and dissemination (disseminate). The data collection technique used in this study is the method of observation, instrument validation, and interviews. The assessment instrument was validated with a content validity ratio approach, then its reliability was tested with the SPSS-assisted Cronbach Alpha test. Research Results a) The PTS Assessment Instrument for collaborative projects between subjects obtained an average of 3.67 from the validator. The average validation score is in the very good category. Based on the results of the validation, it can be concluded that the instrument to be used is valid. b) The reliability test of the PTS assessment instrument for the collaboration project between subjects in 7th grade boys and 7th graders obtained Cronbach's alpha reliability coefficient values of 0.749 and 0.774, respectively, where both values were between 0.7 and 0.9 so that it could be concluded that the instrument to be used has high reliability.Keywords: Project Based Learning, Subjects Collaboration, Sekolah Penggerak, Research Instruments